Neonatal Sequential Organ Failure Assessment (nSOFA) Score Predicts Mortality and Morbidity in Preterm Infants - Shahana Akter; Fatema Begum; Mohammad Golam Sadik; Ayesha Siddika; Rumpa Mani Chowdhury; Mannan, M A (Bangladesh Medical Journal, 2026)
Preterm infants are highly vulnerable to organ dysfunction and death due to physiological immaturity and complications such as respiratory distress syndrome (RDS), sepsis, and intraventricular hemorrhage (IVH). The neonatal Sequential Organ Failure Assessment (nSOFA) score is an emerging tool for evaluating organ dysfunction.This cross-sectional study was conducted from January 2024 to December 2024 in the Department of Neonatology, Bangladesh Medical University (BMU). The study was designed to evaluate the role of the nSOFA score in predicting mortality and morbidity among 60 preterm infants admitted to the Neonatal Intensive Care Unit (NICU), BMU. An additional aim was to identify demographic and clinical factors associated with adverse outcomes in these preterm infants. Demographic, perinatal, and clinical data were collected. nSOFA scores comprising respiratory, cardiovascular, and hematologic components were calculated within 72 hours of birth. Infants were followed until discharge or death. Survivors and non-survivors were compared using independent t-test and chi-square test. Multivariate logistic regression identified independent predictors of mortality. Of the 60 infants, 86.7% survived, and 13.3% died. Non-survivors had significantly lower gestational age (32.8 ± 2.7 vs 34.9 ± 2.3 weeks; p = 0.041) and birth weight (1.8 ± 0.4 vs 2.2 ± 0.5 kg; p = 0.033). Sepsis (75.0% vs 30.8%; p = 0.025), RDS (75.0% vs 19.2%; p = 0.004), bronchopulmonary dysplasia (BPD) (50.0% vs 3.8%; p = 0.008), patent ductus arteriosus (37.5% vs 9.6%; p = 0.045), necrotizing enterocolitis (25.0% vs 3.8%; p = 0.049), and IVH (37.5% vs 7.7%; p = 0.031) were significantly more common among non-survivors. Mean cardiovascular (3.4 ± 1.1 vs 1.2 ± 0.8), respiratory (3.7 ± 0.9 vs 2.1 ± 1.0), hematologic (2.5 ± 0.6 vs 1.6 ± 0.7), and total nSOFA scores (8.1 ± 1.5 vs 4.9 ± 2.2) were significantly higher in non-survivors (all p ≤ 0.002). Multivariate analysis showed final nSOFA score (aOR 1.85; 95% CI 1.32–2.58; p < 0.001), sepsis (aOR 3.10; p = 0.030), BPD (aOR 4.50; p = 0.026), and IVH (aOR 4.20; p = 0.035) independently predicted mortality. The nSOFA score is a strong independent predictor of mortality in preterm infants. Higher early organ dysfunction scores, along with sepsis, BPD, and IVH, significantly increase death risk. Routine nSOFA assessment may support early risk stratification and targeted intervention in NICU settings. Bangladesh Med J. 2025 Sept; 54(1): 17-22